(untitled) (Academia Journal of Medicine, 2019)
Background: The clinical history of the disease is quite variable; there is usually a slow physiological deterioration, but in some patients there is a faster decline in lung function and death occurs within 6-12 months after diagnosis. Others experience an acute exacerbation during the course of the disease with a sudden worsening of respiratory symptoms, hypoxemia and the appearance of new radiological infiltrates without an identifiable cause. Despite different types of clinical course, IPF is inevitably associated with a poor prognosis, with a median survival of 2- 3 years. Subjects and Methods: Age, sex, occupation, address (including phone number) was noted down. A detailed occupational history was sought, enquiring about the age at start of the occupation, exact nature of work, any history of exposure to fumes, gases, dust, etc, any other person in the work place suffering from similar complaints etc were obtained. Results: Majority of the patients were treated with steroids alone 22(62.8%). 10(28.5%) patients were treated with steroids with azathioprine. 3(8.5%) patients were treated with pirfenidone. Conclusion: Majority of the patients, 17(48.5%) out of 35 patients, expired during the study period. 5(14.2%) patients were lost to follow up and the outcome was not available. 10(28.5%) patients remained stable, while 3(8.5%) patients worsened. None of the patients improved during the study period.